Effectiveness of Acting Regional Heads After Simultaneous Regional Head Elections in Indonesia - Hadita, Cynthia (Ultimate Journal of Legal Studies, 2025)
This study aims to analyze the effectiveness of acting regional heads in carrying out government duties after the simultaneous regional head elections (Pilkada) in Indonesia. The research method used is the socio-legal method, which combines a normative and empirical approach to examine the laws and regulations that govern the mechanism for the appointment of acting regional heads and their implementation in practice. Data were collected through document studies, in-depth interviews with relevant stakeholders, in several regions that experienced the appointment of Acting Regional Heads. The results of the study showed that the effectiveness of Acting Regional Heads was influenced by several factors, including the personal competence of the Acting Regional Head, local bureaucratic support, and political legitimacy provided by the community and political parties. Although normatively the Acting Regional Head has the same authority as the definitive regional head, in practice there are often obstacles such as limited authority in strategic decision-making and intervention from the central government and political parties. This study recommends improving regulations and strengthening the supervision mechanism to increase the effectiveness of the implementation of the duties of the Acting Regional Head in maintaining the sustainability of the regional government after the simultaneous Regional Elections. Keyword: Officials, Regional, Effectiveness, Strategic.